Estudo dos dispositivos retóricos em La promenade Vernet, de Denis Diderot - Dezen, Rômulo Titton (2018)
Denis Diderot, the author of a vast and multidimensional work, is a renowned personality to the Human Sciences. Promenade Vernet, an integral part of the 1767 Salon, reflects the complexity of the work of the philosopher in its entirety as we can observe some traces of genres such as fiction, essay, and criticism. The short text is a "walk" in which Diderot masterfully describes a series of seven "sites" under the pretext of questioning various subjects of a philosophical and aesthetic nature. What the reader does not have access to - and only learns at the end - is that descriptions of landscape elements do not refer to seven campaigns, but to seven paintings by the famous French landscape artist, Joseph Vernet. During the "Walk", Diderot and the abbé, his interlocutor and fictitious character, discuss dramatically, in long journeys, the beliefs about art, the position of man in the world and morality. This research aims to highlight the rhetorical devices used by the author, especially ekphrasis and hieroglyph, both associated, directly or indirectly, with the relationship between verbal and imagery (ut pictura poesis). For the development of the research, authors from different periods are used, such as Horace (18 b.C.), who coined the term ut pictura poesis; Lessing (1768), which was fundamental to the development of rhetoric; and Lichtenstein (1994), whose work traces an in-depth journey into the history of rhetoric of figures and on which this memoir is based with a certain accent. In Diderot's text, we note a significant importance of classical texts in other that articles that enlighten this perspective in Diderot’s work were chosen to constitute the research. Apart from this theoretical apparatus, it is appealed to texts composing the work of Diderot which are not part of the 1767 Salon, as well as the Letter on the Deaf and Dumb, for the Use of those who hear and speak, in which we find the expression "hieroglyph" for the first time. In addition to the texts of the critic philosopher, we use a rich critical and essentially French fortune that applies to the study of the work of Diderot, including Bukdahl (1980), Chouillet (1987), Starobinski (1991) and Delon (1995). In this work is also possible to find some exploration of aesthetics and painting, given the plural nature of the text that has been object of study. After this research, one can have a further understanding of the relationships between the visual and the written. Finally, and therefore, the examination of this author and his text highlights what the Salons was, a literary genre created in the eighteenth century, which has caused significant duplication towards modern art and literature despite its one-century duration.